Utilization of Unused Autoclaves to Produce Aquades (Aquabits) in the Laboratory of Biosciences and Plant Technology, Department of Biology, Faculty of Science ITS - Christin Risbandini (Labor Dasar dan Sentral Universitas Andalas, 2020)
Laboratories in Higher Education have an important role as executors of its Tri Dharma which includes the functions of education, research, and community service. Every activity in the laboratory, it requires destilled water as solvent and cleaners of various tools and materials. This fact leads to high budget is needed for the availability of the material in laboratory. In the Plant Biosciences and Technology Laboratory, an autoclave was broken. It is no longer used as its main function sterilization and can only be used as a tool to heat water. With few modifications, namely the addition of a condenser made of copper pipes, the autoclave has been converted into a simple distillation device. It was expected tha the tool could produce distilled water, which has the same value as distilled water sold in the market. The results showed that the tool produces colorless, odorless, and tasteless distilled water. The quality is in accordance with distilled water sold in the market and SNI standard for demineralized water. The pH and TDS values ​​ are slightly higher than distilled water sold in the market but are still in the range of ​ SNI standard for demineralized water. The value of DHL, both the distilled water produced and the one sold in the market are not in the range of SNI standard for demineralized water. Hence, studies are needed to obtain the same value so that the need for distilled water for educational, research, and community service activities in the Department of Biology FSAINS ITS can be fulfilled.